The French Invasion of Egypt and the Rise of Ottoman – Russian – British Alliance 1798-1799 - Mohammed, Ibtisam; Tawfeeq, Hoger; Murad, Khalil (Humanities Journal of University of Zakho, 2022)
The French invasion of Egypt in 1798 was an important historical event, not in the history of Egypt alone, but that of the Ottoman state and its relations with European states, especially Russia and Britain. The Ottoman state was concerned with many internal problems, and sultan Selim III (1789-1807) realized that his country needs an alliance with the enemies of France in Europe to get the French forces out of Egypt. The sultan’s task was not difficult, because the French invasion of Egypt alarmed both Russia and Britain. Russia was concerned by the expansion of French influence in the Mediterranean and the Adriatic Sea, While Britain considered the French occupation of Egypt as a direct threat to British important colony in India. The Ottoman – Russian alliance concluded in December 1798, and the Ottoman – British alliance in January 1799. The last one was more important than the first alliance because the task of getting the French forces out of Egypt carried out by the Ottomans and British forces.